PERBEDAAN LUARAN MOTORIK PASIEN SINDROMA GUILLAIN BARRE DENGAN TERAPI IVIG DAN PLASMAFERESIS - Nurhayati, Wulantika (PERDOSNI, 2025)
ABSTRACT Introduction Guillain-BarrÃƒÂ© syndrome (GBS) is an acute autoimmune polyneuropathy characterized by progressive motor weakness and potentially fatal complications. In severe cases (disability scale Ã¢â€°Â¥3), the standard immunotherapies are intravenous immunoglobulin (IVIg) and plasmapheresis. Studies on populations dominated by demyelinating subtype reported equal efficacy between both treatments, whereas studies on the axonal subtype indicated better motor outcomes with IVIg. However, to the best of our knowledge, such research has not been conducted in Indonesia. Aim To evaluate the difference motor outcomes between GBS patients treated with IVIg and plasmapheresis. Methods A retrospective cross-sectional study was performed using medical records of adult GBS patients admitted between November 2020 and September 2024. Clinical characteristics and Medical Research Council (MRC) motor scores at admission and discharge were analyzed. Motor outcome was categorized as Ã¢â‚¬Å“goodÃ¢â‚¬Â (MRC Ã¢â€°Â¥36) or Ã¢â‚¬Å“poorÃ¢â‚¬Â (MRC <36). Results Among 141 GBS patients, 12 received IVIg and 47 underwent plasmapheresis, and the rest were given supportive therapy and roborantia. The largest proportion was axonal subtype (43,3%). The proportion of good motor outcomes was higher in the IVIg group (83.3%) compared to the plasmapheresis group (59.6%), although this was not statistically significant (p>0.05). Lower initial MRC scores and higher mEGOS and EGRIS scores were associated with poorer outcomes. Discussion IVIg tends to yield better motor outcomes, particularly in GBS axonal subtype. Early identification of GBS subtype is beneficial for treatment decision. Bigger sample sizes and prospective studies are needed to confirm these results. Keywords Guillain-BarrÃƒÂ© Syndrome, IVIg, Motor Outcome, MRC Score, Plasmapheresis